Needs Analysis of STEM-Based Teaching Materials on Integrated Pest Management as a Sustainable Agriculture Solution in The Green Lifestyle Practice Course - Martitik, Dwiyani Anjar (Education, Science, and Technology International Conference, 2025)
Agricultural issues in the modern world, particularly the negative environmental impacts of pesticides use, demand innovation in education. This study aims to analyse the need for integrated pest management (IPM) learning materials as a solution for sustainable agriculture to support learning in the Green Lifestyle Practice course. The research employed a descriptive qualitative method using purposive sampling through structured interviews distributed via Google Forms to 20 students who had taken the Green Lifestyle Practice Course during the even semester of the 2024/2025 academic year. The analysis results indicate that the importance of developing STEM-Based IPM teaching Materials. The findings of this study serve a crucial foundation for subsequent research focused on developing the STEM-Based IPM learning materials to enhance the learning process.